GERAKAN GOTONG ROYONG MELALUI PROSESI KURBAN DALAM PERAYAAN IDUL ADHA: The Gotong Royong Movement through the Qurban Procession during Eid Al-Adha Celebrations - Aminullah Aminullah; Abdurahim Abdurahim; R. Didi Kuswara; Reza Zulaifi; M. Zainuddin; Redy Argito (Yayasan Al-Amin Qalbu, 2026)
The celebration of Eid al-Adha embodies both strong spiritual and social dimensions through the observance of the sacrificial ritual “qurban”. This community service initiative aims to preserve the culture of “gotong royong” (mutual cooperation) within the community, spanning the entire process from the ritual slaughter to the distribution of the sacrificial meat. The project employed a participatory approach—specifically Participatory Action Research—actively involving all segments of the community from the planning stage through to the final distribution of the meat. The results demonstrate that the sacrificial ritual successfully served as an effective unifying force within the community. The spirit of mutual cooperation was particularly evident during the stages of slaughtering and meat distribution. Celebrations and traditions serve as vital opportunities to foster community awareness, compassion, a sense of togetherness, and the spirit of mutual cooperation. Such observances and traditions must be preserved to ensure the community continues to nurture unity and cohesion, especially in an era where there is a growing preference for instant solutions—such as outsourcing the slaughter to professional butchers or paid, exclusive facilities—which can diminish opportunities for communal togetherness.